Gondauri Index (GI): Methodology for a Clay Millennium-Problems-Driven Macro-Financial Index - Davit Gondauri (SSRN, 2025)
The Gondauri Index (GI) is introduced as a novel macro-financial composite index, grounded in the Millennium Development Goals and applied to economic modeling. It integrates three sub-indices: the Inequality-Ricci Subindex (IRS), measuring income distribution stability through Ricci flow dynamics; the Liquidity-Navier-Stokes Resilience (LNSR), capturing systemic robustness via fluid dynamics analogies; and the Inflation FPAS+ζ Credibility (IFC), enhancing inflation forecasting through hybrid FPAS-Riemann zeta methods. Each subindex is normalized on a 0-100 scale, with the final GI computed as a weighted geometric mean (35% IRS, 35% LNSR, 30% IFC). The methodology combines statistical calibration, normalization, and error-reduction benchmarks to ensure reliability and policy applicability. The GI provides a consolidated, forward-looking metric for evaluating inequality, financial stability, and inflation expectations, offering policymakers and researchers a robust tool for decision-making in complex socioeconomic environments.
Keywords: 330; Gondauri Index; Ricci Flow; Navier-Stokes; Riemann Zeta; Inequality; Liquidity; Inflation Forecasting; Macro-Financial Index